Meaning and Discourse of Oral Tradition “Basan” of Helong Language - Maria Osmunda Eawea Monny; Dominikus Tauk (Pioneer: Journal of Language and Literature, 2021)
This research examined the meaning and discourse of a tradition named Basan. Halliday‘s approaches of discourse analysis was used in this research, and was organized around three generalized semiotic meanings that relate to social action (field), roles of people (tenor), and organization of the text or sign (mode). Carrying out the maintenance and revitalization of oral literature was done objectively. “Basan” is a rhythmic traditional speech that is uttered with different intonations in order to convey the main points of speech that is spoken according to the context in order to see the meaning contained in each speech and the context associated with the text spoken. The context in oral tradition “Basan” includes place, time, results and message, which begins with an opening and ends with closing, while the meaning that can be applied in the oral tradition “Basan” are lexical and contextual meanings. “Basan” consists of context and flow, those are opening, main utterance, and closing. For its discourse, “Basan” is done verbally (mode), done by the leaders of the village to the guests in social occasion and by the priest to the assembly in religion occasion (tenor), and done in a social interaction and spiritual activities (field).